SEED 2: a user-friendly platform for amplicon high-throughput sequencing data analyses - Vetrovský, Tomáš; Baldrian, Petr; Morais, Daniel (Bioinformatics (Oxford, England), 2018)
MOTIVATION: Modern molecular methods have increased our ability to describe microbial communities. Along with the advances brought by new sequencing technologies, we now require intensive computational resources to make sense of the large numbers of sequences continuously produced. The software developed by the scientific community to address this demand, although very useful, require experience of the command-line environment, extensive training and have steep learning curves, limiting their use. We created SEED 2, a graphical user interface for handling high-throughput amplicon-sequencing data under Windows operating systems. RESULTS: SEED 2 is the only sequence visualizer that empowers users with tools to handle amplicon-sequencing data of microbial community markers. It is suitable for any marker genes sequences obtained through Illumina, IonTorrent or Sanger sequencing. SEED 2 allows the user to process raw sequencing data, identify specific taxa, produce of OTU-tables, create sequence alignments and construct phylogenetic trees. Standard dual core laptops with 8 GB of RAM can handle ca. 8 million of Illumina PE 300 bp sequences, ca. 4 GB of data. AVAILABILITY AND IMPLEMENTATION: SEED 2 was implemented in Object Pascal and uses internal functions and external software for amplicon data processing. SEED 2 is a freeware software, available at http://www.biomed.cas.cz/mbu/lbwrf/seed/ as a self-contained file, including all the dependencies, and does not require installation. Supplementary data contain a comprehensive list of supported functions. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: mikrobiota; Phylogeny; genetické markery; analýza dat; Software; software; Data Analysis; Genetic Markers; Microbiota; sekvenční seřazení; fylogeneze; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing; Sequence Alignment